Polyphonic discourses in the Hong Kong press: a diachronic analysis of media attitudes towards the One Country, Two Systems policy - Qingyu Gao; Dezheng Feng William (Humanities & Social Sciences Communications)
Abstract The One Country, Two Systems policy (OCTS), which is the cornerstone for the establishment of the Hong Kong SAR in 1997, has been subjected to varying and changing interpretations and opinions in Hong Kong society. Against this backdrop, this study examines the attitude variations and changes towards OCTS in three major Chinese newspapers in Hong Kong from 1997 to 2020. Utilising the Appraisal system and discourse analysis, the study reveals the complexity of attitudes exhibited by different newspapers in response to social dynamics. Oriental Daily News adopted the official voice of the Chinese government, legitimising OCTS and using it as a normative standard for de/legitimising social events and behaviours. Ming Pao consistently adopted an impartial stance, representing OCTS as a topic for debate and covering the varying perspectives of different parties. Apple Daily acknowledged the framework of OCTS but criticised that it was distorted by the authorities. It normalised the “death” of OCTS and legitimised resistant behaviours as defending its spirit. The study uncovers the deliberate choices of attitudes in news coverage, which reveals the newspapers’ different stances and changing discursive strategies. Situated in the unique context of Hong Kong, the study sheds new light on the complex and diverse trajectories of discursive shift, which together constitute a “polyphony” of media attitudes.